PENGARUH RELIGIUSITAS ISLAM TERHADAP STRES PENGASUHAN PADA IBU YANG MEMILIKI ANAK USIA DINI - Nadia Rindila; Alifa Asyafila Rahmadani (IMTIYAZ: Jurnal Ilmu Keislaman, 2026)
Mothers with young children are vulnerable to parenting stress due to the many demands and responsibilities they face, which extend beyond household tasks to childcare. Early childhood is often considered a challenging developmental stage because children are highly dependent on their parents while also seeking independence and exploring their environment. This condition can make children difficult to manage and prone to tantrums, which may increase emotional strain and stress in mothers. If parenting stress is not properly managed, it can negatively affect the well-being of the mother, the child, and the overall family environment. Islamic religiosity is often associated with coping mechanisms for stress because religious beliefs and practices can provide emotional support, guidance, and psychological comfort when individuals face difficult situations. Therefore, this study aims to examine the relationship between Islamic religiosity and parenting stress among mothers with young children and to analyze the contribution of Islamic religiosity to parenting stress. This research used a quantitative method with convenience sampling involving 125 Muslim mothers who have children aged 2–6 years. The instruments used were the Muslim Religiosity Scale developed by Amir (2021) and the Parental Stress Scale developed by Berry and Jones (1995). Regression analysis showed a negative coefficient of -1.048 with an R-square value of 0.163, indicating that Islamic religiosity explains 16.3% of parenting stress.